PENGADAAN TANAH MELALUI PRANATA ADAT DI PROVINSI BENGKULU (Kajian Dalam Hukum Dan Ekonomi) - Imam Mahdi (AL IMARAH : JURNAL PEMERINTAHAN DAN POLITIK ISLAM, 2018)
Abstract: Soil is the main thing in business in the plantation sector, but the way to obtain it is difficult because of the conditions. Between positive law and customary law in the way ownership of land by investor for plantation business will be an obstacle, HGU (Business Use Rights) issued by the government contain elements of legal certainty in positive law, while in absolute law over land, but the hereditary rights can not just disappear or go away. Land acquisition by investors through customary law will find obstacles in legal certainty, because it is difficult to later be slashed, sold and so on. The world of plantations is an economic world that can be traded.Keywords: Land Acquisition, Customary Law